Effect of 4, 4′-stilbenedicarboxylic acid-intercalated layered double hydroxides on UV aging resistance of bitumen. Issue 116 (5th November 2015) - Peng, Chao; Jiang, Guosheng; Lu, Chunhua; Xu, Fang; Yu, Jianying; Dai, Jing
Abstract : UV aging is the main cause of the deterioration of bitumen pavement. Abstract : UV aging is the main cause of the deterioration of bitumen pavement. To mitigate the aging process, a nanohybrid prepared by intercalation of 4, 4′-stilbenedicarboxylic acid (SA) into Zn/Al layered double hydroxide (LDH) was blended with styrene-butadiene-styrene (SBS) bitumen. The results of X-ray diffraction, Fourier transform infrared spectroscopy (FTIR) and transmission electron microscopy showed that SA anions have been successfully intercalated into the LDH galleries and the interlayer distance of LDH increased from 0.76 nm to 1.37 nm. UV-vis spectroscopy measurement revealed that the Zn/Al LDH intercalated with SA anions (Zn/Al–SA-LDH) has a synergistic effect on reflecting and adsorbing UV light. The physical tests, FTIR analysis and atomic force microscopy images of the bitumen specimens proved that the UV aging resistance of SBS modified bitumen can be significantly enhanced by Zn/Al–SA-LDH.